2015
DOI: 10.1039/c5gc00503e
|View full text |Cite
|
Sign up to set email alerts
|

“On water” direct catalytic vinylogous Henry (nitroaldol) reactions of isatins for the efficient synthesis of isoxazole substituted 3-hydroxyindolin-2-ones

Abstract: An efficient “on water”-promoted direct catalytic vinylogous Henry reaction is described, giving products in excellent yields and diastereoselectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…However, the results are inconsistent with the experimental research, in which the reaction rate in water is faster than those in THF and methanol. 29 Whereaer, for the rate-determining step of Path A in water, microsolvent models with the introduction of one-, three-, and up to six-water clusters to the reaction centers were employed to simulate the local microhydration surrounding (the corresponding geometry structures of the reactants, transition states, and intermediates are given in Fig. S4 of the ESI †).…”
Section: Effects Of Solvents Studied By Dft Calculations With the Smdmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the results are inconsistent with the experimental research, in which the reaction rate in water is faster than those in THF and methanol. 29 Whereaer, for the rate-determining step of Path A in water, microsolvent models with the introduction of one-, three-, and up to six-water clusters to the reaction centers were employed to simulate the local microhydration surrounding (the corresponding geometry structures of the reactants, transition states, and intermediates are given in Fig. S4 of the ESI †).…”
Section: Effects Of Solvents Studied By Dft Calculations With the Smdmentioning
confidence: 99%
“…Therefore, effective methods for direct vinylogous Henry reactions have been discovered and explored in recent years. 29,30 In 2015, Zhang et al rst reported the vinylogous Henry reaction between isatin and 3,5-dialkyl-4-nitroisoxazole, leading to isoxazole-substituted 3-hydroxy-2-oxindole derivatives, medicinally important compounds, using water as the solvent for optimizing the reaction conditions at room temperature. 29 They found that organic base catalysts are more effective than inorganic bases and 1,4-diazabicyclo [2.2.2]octane (DABCO) is the optimal catalyst with a near quantitative yield (>99%) in 1.5 hours for the synthesis of the desired vinylogous product.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The utilization of “safer solvents” and “design for energy efficiency” can be considered two key principles of the 12 principles of green chemistry . Recent researches show that water is a promising medium for catalysis . Moreover, some reactions in aqueous media also achieve rate acceleration and higher yield as compared to the cases in organic solvents .…”
Section: Introductionmentioning
confidence: 99%